EFFECTS OF CURING TEMPERATURE AND ATMOSPHERE ON THE PROPERTIES OF ISOTROPIC BONDED NdFeB MAGNETS. - Toto Sudiro; Agus Sukarto Wismogroho; Perdamean Sebayang (Jurnal Sains Materi Indonesia, 2015)
EFFECTS OF CURING TEMPERATURE AND ATMOSPHERE ON THE PROPERTIES OF ISOTROPIC BONDED NdFeB MAGNETS. The purpose of this paper was to synthesize the isotropic bonded NdFeB magnets at varying curing temperature and atmosphere, and to clarify their properties. For the aforesaid objective, the NdFeB powder was mixed with polyacrylate binder (3wt%) and compacted by hydraulic pressure with a compressive pressure of 30 MPa. The specimens were then separately cured at 100, 150, 180 and 200°C for 1 h in air and vacuum. The effects of curing temperature in air and vacuum on the bulk density and magnetic properties of isotropic bonded NdFeB magnets were studied. The results indicated that the bulk density and fluxmagnet density of bonded NdFeB magnets decreased with increase in curing temperature. This seems to be due to the binder vaporization and oxidation of element of NdFeB magnet. The bulk density of specimens cured in air was higher than that in vacuum for all temperatures. On the contrary, the magnetic flux density showed the opposite behavior. The optimum magnetic properties were achieved at curing temperature of 100oC for 1 h in vacuumwith Br = 6,61 kG, HCJ = 8,841 kOe, and BHmax = 9,01 MGOe.